A Morphological Analysis Derivational Suffix On ‘Six Minutes English’ Audio Conversation Of Bbc Learning English Entitled “The Bond Between Sisters” - Agnia, Sabila; Meidi Kulsum, Eva (UIN Sunan Gunung Djati Bandung, 2025)
This study aims to find out the derivational suffixes that appear in audio conversations and understand their functions. The methodology used descriptive qualitative. The data are words taken from conversation audio. The data source of the study is audio conversation of BBC Learning English entitled “The Bond Between Sisters”. The data taken by 1). listening to the audio several times for words that may contain derivational suffixes in the audio 2). Making a transcript of the audio and matching the transcript with the audio. 3). Reading through the transcript and highlighted all words containing derivational suffix 4). Listing all the derivational suffixes found into derivational types 5). Rereading the transcript to ensure no derivational suffix words were missed. Data were analyzed through following steps: 1). Collecting then identifying every word that contains derivational suffix. 2). Classifying and categorizing derivational suffix based on its type and function. 3). Determining the lexical changes and meanings of the derivational suffixes found in the audio. The result of the study showed that there are 31 derivational suffixes words with three forms of derivational suffix. The three types of derivational was found are nominal suffix, adverbial suffix and adjectival suffix. The researcher also found 7 words formation, they are Verb → noun, Adjective → adverb, Noun → adverb, Verb → adjective, Noun → adjective, Adjective → noun, Verb → adverb.